Needs Assessments “Increasing Access of the Underserved Areas in Palestine” - Mohammad Qtait, RN, MSN,, Dr. Sumaya Y. Sayej, RN,MSN, PhD, (International Journal of Innovative Research in Medical Science, 2017)
The socio-demographic profile of the surveyed population and the living conditions are very significant which indicate the availability and persistence of early and interfamily marriage, coupled with large and low income families in overcrowded houses. The living conditions of the surveyed population indicates the harsh circumstances they go through and how really they are underserved in basic living circumstances, health care facilities, services and professionals to meet their needs, because of restriction in movement, being in a remote area and under served for living in area C. The study results were concluded from the quantitative data and qualitative analysis. The quantitative data results showed the need for comprehensive health care services because of poverty, lack of medical insurances, and difficulty in accessibility to these services, meanwhile 70.2% of the participants asked for ambulance services where it deemed necessary particularly in emergency cases. Also, the participants pinpointed that 0.3% is the service of the mobile clinic which mainly comes to the remote areas for child vaccination only. This indicates the need of well-equipped mobile clinics to provide a wide range of health services that are in need in the remote underserved areas. The qualitative data results showed the urgent need for MCH services to meet the needs of the target population. Comprehensive services around the clock especially for maternity care and in case of emergencies should be ensured. The qualitative data also indicated that pediatric and child health services are greatly required. Adolescents need health education/promotion programs to help them develop their knowledge and attitude towards SRH matters. Also they asked for units within the SDP clinics which meet their needs and have free access for them. All interviewees reiterated on the reasons why these services are needed; difficulties in accessing health care facilities outside their areas of residence because of military presence check points, and the separation wall. They further commented on PFPPA-SDPs being located in the cities, long distances require lot of expenses for public transportation and lack of ambulances with all these circumstances makes it very difficult to reach.